Corporate social disclosures: a user perspective on assurance. Issue 5 (2nd June 2014) - Wong, Renfred; Millington, Andrew
Abstract : Purpose: – The purpose of this paper is to investigate corporate social disclosure (CSD) assurance from a stakeholder perspective within a study which encompasses both stakeholder preferences and demand drivers of CSD assurance. Design/methodology/approach: – Stakeholder perceptions of and their demand for CSD assurance are examined through a questionnaire survey. The analysis is based on responses in an empirical study from 147 organisations which are investing, procuring and third-sector stakeholders. Findings: – Overall, stakeholder comments suggest an emphasis on the importance of specialist environmental assurors and the role of trust. The demand for assurance is positively related to stakeholders' assessment of the value of CSD and the use of information from information intermediaries such as responsible investment indices, and negatively related to stakeholder perceptions of CSD representational faithfulness. Research limitations/implications: – This paper only draws on data from the UK. Similar research can be explored in a context outside the UK. Practical implications: – Better understanding of stakeholder defined determinants of the demand for CSD assurance as well as their perceptions of CSD assurance will inform regulators and enable companies to better discharge accountability towards stakeholders. Originality/value: – This is one of the few empirical studies that investigate CSD assurance and one of the first to focus on stakeholder perceptions of, and demand for, CSD assurance within a multiple stakeholder perspective, rather than practitioner or corporate perceptions of CSD assurance.